Method for producing ethylene-vinyl alcohol copolymer
The described method addresses impurity removal challenges in ethylene-vinyl alcohol copolymer production by using alcohol solvent saponification, concentration, and multiple water washings, resulting in improved efficiency and reduced wastewater.
Patent Information
- Application Number
- JP2023544399
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-09-26
- Filing Date
- 2022-09-27
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-09-27
AI Technical Summary
Existing methods for producing ethylene-vinyl alcohol copolymer face challenges in efficiently removing impurities, particularly when excessive alkaline catalysts are used, leading to increased wastewater generation and reduced production efficiency.
A method involving saponification of ethylene-vinyl acetate copolymer in an alcohol solvent, followed by concentration, cooling, pulverization, and multiple water washings to produce a highly purified ethylene-vinyl alcohol copolymer.
This method significantly improves cleaning efficiency, minimizes wastewater generation, and enhances production efficiency by producing a highly pure ethylene-vinyl alcohol copolymer with reduced impurities.
Smart Images

Figure 0007618349000003 
Figure 0007618349000001 
Figure 0007618349000002
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0185017 filed on December 22, 2021 and Korean Patent Application No. 10-2022-0121584 filed on September 26, 2022, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to a method for producing an ethylene-vinyl alcohol copolymer. [Background technology]
[0003] Ethylene-vinyl alcohol copolymer (EVOH) has excellent barrier properties against oxygen and other gases, transparency, oil resistance, antistatic properties, and mechanical strength, and is widely used as a material for films, sheets, containers, etc.
[0004] EVOH can be produced by saponification of ethylene-vinyl acetate (EVAc), which is produced by copolymerization of ethylene and vinyl acetate. Specifically, a commonly known production method includes saponifying EVAc in the presence of an alkaline catalyst, extruding the polymer component, forming it into pellets, and then washing and drying the pellets to remove the catalyst and reaction by-products remaining in the pellets.
[0005] However, this method has the disadvantage that it is difficult to remove impurities from the pellets. In particular, when an excessive amount of alkaline catalyst is used to increase the degree of saponification of EVOH, the content of catalyst impurities in the pellets also increases, and in order to sufficiently remove these, an excessive washing process is required, which generates a large amount of wastewater and reduces the overall production efficiency. In addition, if the size of the pellets is reduced to increase the efficiency of the washing process, the productivity of the extrusion and pelletization processes decreases, which is also undesirable in terms of production efficiency. Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made to solve the above problems, and an object of the present invention is to provide a method for producing an ethylene-vinyl alcohol copolymer, which can improve the efficiency of a washing process and minimize the amount of wastewater generated. [Means for solving the problem]
[0007] Therefore, according to one embodiment of the present invention, Ethylene-vinyl acetate copolymer was treated with alkali catalyst and C 1-4 saponification in the presence of an alcohol solvent to obtain a reaction mixture comprising an ethylene-vinyl alcohol copolymer; The reaction mixture was concentrated, and then water was added to the mixture. 1-4 preparing an ethylene-vinyl alcohol copolymer solution having an alcohol and water weight ratio of 1:9 to 9:1 and a solid content of 10% by weight to 25% by weight; cooling the ethylene-vinyl alcohol copolymer solution to produce an ethylene-vinyl alcohol copolymer cake in which the ethylene-vinyl alcohol copolymer is solidified; pulverizing the ethylene-vinyl alcohol copolymer cake to obtain an ethylene-vinyl alcohol copolymer pulverized product; and washing the pulverized material with water; The present invention provides a method for producing an ethylene-vinyl alcohol copolymer, comprising: Effect of the Invention
[0008] According to the present invention, a high purity ethylene-vinyl alcohol copolymer can be produced through a simple washing process compared to the conventional manufacturing method, and therefore, according to the present invention, the production efficiency of the ethylene-vinyl alcohol copolymer can be increased and the amount of wastewater generated in the washing process can be minimized. [Brief description of the drawings]
[0009] [Figure 1] 1 illustrates an example of an apparatus capable of carrying out the method for producing an ethylene-vinyl alcohol copolymer of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In this specification, the terms "include", "comprise", "have" and the like are intended to specify the presence of an implemented feature, step, component, or combination thereof, and should be understood not to preclude the possibility of the presence or addition of one or more other features, steps, components, or combinations thereof.
[0011] Although the present invention can be modified in various ways and has various forms, specific embodiments are described in detail below. However, it is not intended to limit the present invention to the specific disclosed embodiments, and it should be understood that the present invention includes all modifications, equivalents, and alternatives falling within the spirit and technical scope of the present invention.
[0012] On the other hand, unless otherwise specified in this specification, the pressure condition is normal pressure (760±50 torr).
[0013] The method for producing an ethylene-vinyl alcohol copolymer of the present invention comprises the steps of: Ethylene-vinyl acetate copolymer was treated with alkali catalyst and C 1-4 saponification in the presence of an alcohol solvent to obtain a reaction mixture comprising an ethylene-vinyl alcohol copolymer (Step 1); The reaction mixture was concentrated, and then water was added to the mixture. 1-4 preparing an ethylene-vinyl alcohol copolymer solution having an alcohol and water weight ratio of 1:9 to 9:1 and a solid content of 10% by weight to 25% by weight (step 2); cooling the ethylene-vinyl alcohol copolymer solution to produce an ethylene-vinyl alcohol copolymer cake in which the ethylene-vinyl alcohol copolymer is solidified (Step 3); pulverizing the ethylene-vinyl alcohol copolymer cake to obtain an ethylene-vinyl alcohol copolymer pulverized product (step 4); and washing the ground product with water (step 5);
[0014] The existing method for producing ethylene-vinyl alcohol copolymer includes the steps of extruding the ethylene-vinyl alcohol copolymer after saponification of ethylene-vinyl acetate copolymer, pelletizing the ethylene-vinyl alcohol copolymer, washing and drying the pelletized ethylene-vinyl alcohol copolymer. However, the pelletized ethylene-vinyl alcohol copolymer has a problem that the washing efficiency is low and several long washing processes are required to sufficiently remove impurities such as catalyst by-products.
[0015] Therefore, the present inventors have studied a method for obtaining a high purity ethylene-vinyl alcohol copolymer from a reaction mixture without an excessive washing process after the saponification reaction of an ethylene-vinyl acetate copolymer, and as a result, have confirmed that the above steps can provide a high purity ethylene-vinyl alcohol copolymer with high efficiency, thereby completing the present invention.
[0016] The present invention will now be described in detail step by step.
[0017] In the present invention, first, an ethylene-vinyl acetate copolymer is reacted with an alkali catalyst and C 1-4 Saponification is carried out in the presence of an alcohol solvent to obtain a reaction mixture containing an ethylene-vinyl alcohol copolymer (Step 1).
[0018] In the present invention, the ethylene-vinyl acetate copolymer, which is a reactant for producing the ethylene-vinyl alcohol copolymer, is a commercially available product or is produced by copolymerizing ethylene and vinyl acetate monomers.
[0019] The ethylene-vinyl acetate copolymer may be a copolymer of ethylene and vinyl acetate with a monomer copolymerizable therewith. Examples of such monomers include α-olefins such as propylene, isobutylene, α-octene, and α-dodecene; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, and itaconic acid, their salts, their anhydrides, and mono- or dialkyl esters; nitriles such as acrylonitrile and methacrylonitrile; amides such as acrylamide and methacrylamide; olefin sulfonic acids such as ethylene sulfonic acid, aryl sulfonic acid, and metaaryl sulfonic acid, or their salts; vinyl monomers such as alkyl vinyl ethers, vinyl ketones, N-vinyl pyrrolidone, vinyl chloride, and vinylidene chloride; and the like.
[0020] The ethylene content of the ethylene-vinyl acetate copolymer can be appropriately adjusted according to the physical properties of the desired ethylene-vinyl alcohol copolymer. For example, in order to ensure the gas barrier properties and melt moldability of the ethylene-vinyl alcohol copolymer, the ethylene content of the ethylene-vinyl acetate copolymer may be, but is not limited to, 20 mol% or more, 25 mol% or more, or 30 mol% or more and 60 mol% or less, 50 mol% or less, or 40 mol% or less.
[0021] On the other hand, the ethylene content is that of an ethylene-vinyl acetate copolymer or an ethylene-vinyl alcohol copolymer. 1 It is calculated from the peak integral ratio of H-NMR data.
[0022] The weight average molecular weight (Mw) of the ethylene-vinyl acetate copolymer is not particularly limited, but may be, for example, 150,000 g / mol or more, 170,000 g / mol or more, or 180,000 g / mol or more and 290,000 g / mol or less, 270,000 g / mol or less, or 250,000 g / mol or less. The weight average molecular weight of the ethylene-vinyl alcohol copolymer obtained by the saponification reaction of the ethylene-vinyl acetate copolymer satisfying the weight average molecular weight may satisfy the range of 110,000 g / mol or more, 120,000 g / mol or more, or 130,000 g / mol or more, and 220,000 g / mol or less, 200,000 g / mol or less, or 190,000 g / mol or less.
[0023] The weight average molecular weight of the ethylene-vinyl acetate copolymer and the ethylene-vinyl alcohol copolymer is measured by gel permeation chromatography (GPC).
[0024] In the saponification reaction of ethylene-vinyl acetate copolymer, an alcohol solvent is usually used, and in the present invention, a lower alcohol having 1 to 4 carbon atoms is used as the solvent. 1-4 Examples of the alcohol include one or more selected from the group consisting of methanol, ethanol, n-propanol, isopropanol, n-butanol, and t-butanol, and preferably, methanol can be used.
[0025] The amount of the alcohol used is not particularly limited, and can be determined depending on the amounts of reactants and reaction conditions.
[0026] The alkaline catalyst may be at least one selected from the group consisting of sodium hydroxide, potassium hydroxide, lithium hydroxide, sodium methoxide, sodium ethoxide, potassium t-butoxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, sodium acetate, potassium acetate, and sodium propionate, and preferably at least one selected from the group consisting of sodium hydroxide, potassium hydroxide, sodium methoxide, and sodium ethoxide.
[0027] In order to smoothly carry out the saponification reaction of the ethylene-vinyl acetate copolymer, the alkali catalyst can be used in an amount of 0.01 mol or more, or 0.015 mol or more and less than 0.05 mol, or 0.04 mol or less, per mol of vinyl acetate units in the ethylene-vinyl acetate copolymer.
[0028] The reaction temperature during the saponification reaction may be 40° C. or more, 50° C. or more, or 60° C. or more, and 120° C. or less, 110° C. or less, or 100° C. or less. If the reaction temperature is less than 40° C., the saponification reaction rate becomes excessively slow, and if it exceeds 120° C., side reactions are likely to occur, so it is preferable to satisfy the above range.
[0029] The reaction pressure during the saponification reaction may be in the range of 0.01 bar or more, or 0.05 bar or more and 0.5 bar or less, or 0.4 bar or less, but is not limited thereto.
[0030] The saponification reaction is carried out under an inert gas atmosphere such as nitrogen or argon, and the reaction can be carried out while continuously discharging the by-product methyl acetate out of the system in order to increase the conversion rate.
[0031] When the saponification reaction progresses and a desired conversion rate is reached, the reaction mixture is neutralized by adding an acid such as acetic acid to terminate the reaction, and then the process of purifying ethylene-vinyl alcohol copolymer from the neutralized reaction mixture (steps 2 to 5) is carried out.
[0032] The neutralization and purification process of the reaction mixture is carried out, for example, using an apparatus as shown in FIG.
[0033] The amount of acid added to neutralize the reaction mixture can be adjusted depending on the amount of alkali catalyst used. For example, 0.9 equivalents or more, or 1.0 equivalents or more and 1.5 equivalents or less, or 1.2 equivalents or less of acid can be added per equivalent of alkali catalyst.
[0034] Next, the neutralized reaction mixture was concentrated, and water was added to the mixture to obtain C 1-4 An ethylene-vinyl alcohol copolymer solution having an alcohol to water weight ratio of 1:9 to 9:1 and a solid content of 10% to 25% by weight is prepared (Step 2).
[0035] Concentration of the reaction mixture is carried out using the C 1-4 The method for evaporating all or part of the alcohol is not particularly limited. For example, the neutralized reaction mixture in the neutralization tank 1 is heated while an inert gas such as nitrogen or argon is blown in to the neutralization tank 1 to evaporate the alcohol. 1-4 The reaction mixture can be concentrated by evaporating the alcohol. The heating temperature is 1-4 The temperature can be appropriately adjusted depending on the composition of the alcohol and the reaction mixture. For example, the temperature may be 35° C. or higher, or 45° C. or higher and 65° C. or lower, or 55° C. or lower, under normal pressure (760 torr). Alternatively, the pressure in the neutralization tank 1 may be reduced and the temperature may be reduced by blowing in an inert gas at a lower temperature. 1-4 The alcohol can be evaporated. C remaining in the reaction mixture after said concentration 1-4 Alcohol is used as a co-solvent in the preparation of ethylene-vinyl alcohol copolymer solutions.
[0036] Water was added to the concentrated reaction mixture as described above, and C 1-4An ethylene-vinyl alcohol copolymer solution is produced in which the weight ratio of alcohol to water is 1:9 to 9:1, or 7:3 to 3:7, or 4:6 to 6:4, and the solid content is 10% by weight or more, or 15% by weight or more and 25% by weight or less, or 20% by weight or less.
[0037] The water may be distilled water or deionized water having an electrical conductivity of 10 μS / cm or less, preferably 5 μS / cm or less. The lower the electrical conductivity of the water, the better, and there is no lower limit, but for example, the electrical conductivity may be 0.1 μS / cm or more, or 0.3 μS / cm or more.
[0038] Said C 1-4 The alcohol may be that which remains after concentration of the reaction mixture or may be added in addition to C during the addition of water to achieve the solvent ratio. 1-4 Alcohol can be further added to produce an ethylene-vinyl alcohol copolymer solution.
[0039] Ethylene-vinyl alcohol copolymer is C 1-4 Although it is difficult to dissolve in alcohol or water alone, as mentioned above, 1-4 It can be dissolved in a solvent in which alcohol and water are mixed in a weight ratio of 1:9 to 9:1. 1-4 An ethylene-vinyl alcohol copolymer solution is prepared using a mixed solvent of alcohol and water, and then cooled and solidified to produce a cake-like ethylene-vinyl alcohol copolymer. When the solvent composition is satisfied, the cake-like solidified ethylene-vinyl alcohol copolymer is pulverized to an appropriate particle size in a later process.
[0040] In the unlikely event that C in the solvent of the ethylene-vinyl alcohol copolymer solution 1-4 If the alcohol content is too low or the solid content is too high (more than 25 wt%), the ethylene-vinyl alcohol copolymer cake may not be easily pulverized in the subsequent process, and therefore the efficiency of the subsequent washing process may be reduced.
[0041] On the other hand, if the water content in the solvent is too low or the solid content does not reach 10% by weight, the ethylene-vinyl alcohol copolymer cake will have insufficient hardness and will not be crushed into crumbs but will be in the form of a slurry, which is difficult to wash, and the ethylene-vinyl alcohol copolymer may escape into fine particles during the washing process, resulting in a high loss rate, which is undesirable.
[0042] Next, the ethylene-vinyl alcohol copolymer solution is cooled to prepare an ethylene-vinyl alcohol copolymer cake in which the ethylene-vinyl alcohol copolymer is solidified (Step 3), which is then pulverized to obtain a crumb (Step 4).
[0043] The pulverized material has a larger surface area than existing ethylene-vinyl alcohol copolymer pellets, and therefore impurities can be removed more effectively during washing with water, making it possible to produce a high-purity ethylene-vinyl alcohol copolymer with a simple washing process.
[0044] The cooling step for obtaining the ethylene-vinyl alcohol copolymer cake is carried out in a temperature range of −15° C. to −1° C., or in a range of −10° C. to −3° C. As an example, the ethylene-vinyl alcohol copolymer solution is placed in a cooling solidification mold 3 and left at −15° C. to −1° C. to obtain an ethylene-vinyl alcohol copolymer cake.
[0045] The crusher 4 used for crushing the cake is not particularly limited, and for example, a low speed crusher, an industrial mixer, an industrial chopper, or other device can be used as the crusher. The average particle size (D50) of the crushed material is preferably 0.1 mm or more, or 0.5 mm or more, and 2.5 mm or less, or 2 mm or less, since this can improve the washing efficiency while preventing the loss of the ethylene-vinyl alcohol copolymer. Since the cake is crushed in a solution, the particle size can be adjusted not only by the crushing conditions but also by the solvent composition and solid content of the solution, and the above-mentioned C 1-4By satisfying the weight ratio of alcohol to water and the range of the solid content, a suitable average particle size of the ground product can be achieved.
[0046] The average particle size (D50) of the pulverized material can be measured using a particle size analyzer, for example, a laser diffraction particle size analyzer (e.g., Microtrac S3500). Specifically, the copolymer powder to be measured is dispersed in a dispersion medium and then introduced into a laser diffraction particle size analyzer. When the particles pass through a laser beam, the difference in the diffraction pattern according to the particle size is measured to calculate the particle size distribution, and the particle size at the point where the particle size is 50% of the cumulative particle volume distribution according to the particle size measured by the measuring device is calculated, thereby obtaining the average particle size (D50).
[0047] Next, the pulverized material is washed with water to obtain a purified ethylene-vinyl alcohol copolymer (Step 5).
[0048] Since the pulverization step is performed in a solution, a step of draining the solution containing the pulverized material using a centrifugal drainer 5 or the like may be performed before washing with water. After that, the pulverized material from which draining has been completed is placed in a washing tank 6, water is added and stirred, and then the liquid is removed using a centrifugal drainer 7 or the like, so that a water washing process can be performed. The water washing process may be performed once, or may be repeated two or more times as necessary.
[0049] The water used in the water washing may be distilled water or deionized water having an electric conductivity of 10 μS / cm or less, preferably 5 μS / cm or less. The lower the electric conductivity of the water, the better, and there is no lower limit, but for example, it may be 0.1 μS / cm or more, or 0.3 μS / cm or more.
[0050] The amount of water added during the water washing is preferably 100 parts by weight or more, or 200 parts by weight or more, or 300 parts by weight or more, and 1,000 parts by weight or less, or 800 parts by weight or less, or 600 parts by weight or less, per 100 parts by weight of the ground material deliquified each time. If the amount of water added is too small, impurities from the ground material cannot be sufficiently dissolved, whereas if the amount of water added is too large, the amount of washing water consumed increases without increasing the washing efficiency, so it is preferable to satisfy the above range.
[0051] The temperature of the water during the washing is preferably 10° C. to 40° C., or 20° C. to 30° C., since impurities can be effectively removed while preventing damage to the ethylene-vinyl alcohol copolymer.
[0052] The pulverized ethylene-vinyl alcohol copolymer has a large surface area and is more efficient in washing than existing pellet-shaped copolymers, so that under the above conditions, more than about 90% or more than about 93.5% of impurities can be removed by one water wash. However, in order to obtain an ethylene-vinyl alcohol copolymer of higher purity, water washing can be repeated two or more times as necessary.
[0053] The number of times the water washing is repeated is not particularly limited, but for example, the water washing may be repeated 2 or more times, or 3 or more times and 7 or less times, or 5 or less times. The number of times the water washing is repeated can be adjusted depending on the amount of ground material to be treated at one time, but generally, under the above conditions, about 99.5% of the impurities are removed by 3 water washings, and about 99.9% of the impurities are removed by 5 water washings. Therefore, when considering the economical and efficient nature of the process, it is preferable to repeat the water washing 7 or less times, or 5 or less times.
[0054] Alternatively, the water washing may be repeated several times until the electrical conductivity of the drained washing liquid is 10 μS / cm or less, or 8 μS / cm or less, preferably 7 μS / cm or less. The electrical conductivity of the washing liquid is a measure of the amount of residual alkali catalyst and impurities contained in the pulverized material, and it can be determined that the lower the electrical conductivity of the washing liquid, the higher the purity of the ethylene-vinyl alcohol copolymer.
[0055] The time for each water wash may be 20 minutes or more, or 30 minutes or more, and 2 hours or less, or 1 hour or less. As will be seen from the examples described later, according to the present invention, the washing efficiency is significantly improved, so that excellent washing effect can be ensured even with a washing time of 2 hours or less.
[0056] The ethylene-vinyl alcohol copolymer obtained after the water washing is completed has a residual sodium content of 30 ppm or less, or 20 ppm or less, or 10 ppm or less, and has a very low impurity content. The lower the residual sodium content, the better, and theoretically it can be 0 ppm.
[0057] According to the above-mentioned manufacturing method, the efficiency of the washing process is significantly improved compared to the conventional manufacturing method of ethylene-vinyl alcohol copolymer, so that a high-purity ethylene-vinyl alcohol copolymer can be manufactured through a relatively simple washing process. Therefore, according to the present invention, the production efficiency of the ethylene-vinyl alcohol copolymer is improved, and the amount of wastewater generated in the washing process can be minimized, thereby reducing environmental pollution.
[0058] Preferred examples are presented below for understanding the present invention, but the following examples are merely for illustrating the present invention and are not intended to limit the present invention thereto.
[0059] <Example> Example 1 Using the apparatus shown in FIG. 1, an ethylene-vinyl alcohol copolymer was produced by the following method.
[0060] 100 parts by weight of ethylene-vinyl acetate copolymer (EVAc, Mw 230,000 g / mol) with an ethylene content of 32 mol% and 400 parts by weight of methanol were placed in a saponification reactor, and 60 parts by weight of a methanol solution of sodium hydroxide (16 g / L) was added. Nitrogen gas was then blown into the reactor, and the saponification reaction was carried out at 60°C for 6 hours while removing the by-product methyl acetate together with methanol from the system, to obtain a reaction mixture containing an ethylene-vinyl alcohol (EVOH) copolymer.
[0061] 15 kg of the reaction mixture was neutralized by adding 42 g of acetic acid (AcOH) (acetic acid / saponification catalyst = 1 / 1 molar ratio) and 0.24 kg of water. Argon gas was blown into the neutralization tank 1, and the reaction mixture was concentrated while removing 10.8 kg of methanol to the outside of the neutralization tank 1 at an internal temperature of 64°C.
[0062] Then, 2.05 kg of water (distilled water, electrical conductivity 4 μS / cm) was added into the neutralization tank 1 to produce an ethylene-vinyl alcohol (EVOH) solution having a weight ratio of methanol to water of 6:4 and a total solids content (TSC) of 15%.
[0063] The EVOH solution was poured into a cooling and solidifying mold 3 and solidified at −8° C. to obtain an EVOH cake.
[0064] Thereafter, the EVOH cake was crushed by a crusher 4 into crumbs having an average particle size (D50) of 1 mm to 1.5 mm.
[0065] The EVOH pulverized material was placed in a centrifugal deliquor 5 to carry out the first deliquor. The EVOH pulverized material after the first deliquor was placed in a washing tank 6, and 500 parts by weight of 25°C water (distilled water, electrical conductivity 4 μS / cm) was added to 100 parts by weight of the EVOH pulverized material, and the mixture was stirred for 2 hours to wash with water, and then placed in a centrifugal deliquor 7 to remove the washing liquid. The water washing and washing liquid removal operation was repeated four more times to perform the water washing operation, and the conductivity of the washing liquid and the sodium content of the EVOH pulverized material were measured each time. At this time, the washing liquid and the EVOH pulverized material in the washing tank 6 were separated at 30 minute intervals for the first three water washings, and at 1 hour intervals for the fourth and fifth water washings, and the electrical conductivity of the washing liquid and the sodium content of the EVOH pulverized material were analyzed.
[0066] After five washing steps were completed, a crumb-like EVOH copolymer having a water content of 70% by weight was finally obtained.
[0067] Example 2 An ethylene-vinyl acetate copolymer having an ethylene content of 32 mol % was saponified in the same manner as in Example 1 to obtain a reaction mixture containing an ethylene-vinyl alcohol (EVOH) copolymer.
[0068] 15 kg of the reaction mixture was neutralized by adding 42 g of acetic acid (AcOH) (acetic acid / saponification catalyst = 1 / 1 molar ratio) and 0.4 kg of water. Argon gas was blown into the neutralization tank 1, and the reaction mixture was concentrated while removing 12.6 kg of methanol to the outside of the neutralization tank 1 at an internal temperature of 100°C.
[0069] Then, 2 kg of water (distilled water, electrical conductivity 4 μS / cm) was added into the neutralization tank 1 to produce an ethylene-vinyl alcohol (EVOH) solution with a weight ratio of methanol to water of 4:6 and a total solids content (TSC) of 20%.
[0070] Thereafter, an EVOH cake was produced and crushed in the same manner as in Example 1, and then washed with water five times to finally obtain a crumb-like EVOH copolymer with a water content of 72% by weight.
[0071] Comparative Example 1 An ethylene-vinyl acetate copolymer having an ethylene content of 32 mol % was saponified in the same manner as in Example 1 to obtain a reaction mixture containing an ethylene-vinyl alcohol (EVOH) copolymer.
[0072] 15 kg of the reaction mixture was neutralized by adding 42 g of acetic acid (AcOH) (acetic acid / saponification catalyst = 1 / 1 molar ratio) and 0.1 kg of water. Argon gas was blown into the neutralization tank, and the reaction mixture was concentrated while removing 13.2 kg of methanol to the outside of the neutralization tank at an internal temperature of 64°C.
[0073] Then, 0.57 kg of water (distilled water, electrical conductivity 4 μS / cm) was added into the neutralization tank to prepare an EVOH solution having a weight ratio of methanol to water of 6:4 and a total solids content (TSC) of 35%.
[0074] The EVOH solution was extruded into a cooling tank filled with water at a temperature of 2° C. using an extruder having a hole with a diameter of 1.8 mm, and solidified into a strand shape. The strand solid was cut with a pelletizer to obtain EVOH pellets with lengths of 1.5 to 2.5 mm.
[0075] The obtained EVOH pellets were placed in a washing tank, and 25°C water (distilled water, electrical conductivity 4 μS / cm) was added and stirred for 2 hours to wash the pellets, and then the pellets were placed in a centrifugal deliquor to drain the washing liquid. The washing and draining of the washing liquid was repeated four more times to perform the washing operation, and the conductivity of the washing liquid drained each time and the sodium content of the EVOH pulverized material were measured. At this time, the washing liquid and the EVOH pulverized material in the washing tank 6 were collected at 30 minute intervals for the first three water washings, and then at 1 hour intervals for the fourth and fifth water washings, and the electrical conductivity of the washing liquid and the sodium content of the EVOH pulverized material were analyzed.
[0076] After five washing steps were completed, a pellet-shaped EVOH copolymer having a water content of 50% was finally obtained.
[0077] Comparative Example 2 An ethylene-vinyl acetate copolymer having an ethylene content of 32 mol % was saponified in the same manner as in Example 1 to obtain a reaction mixture containing an ethylene-vinyl alcohol (EVOH) copolymer.
[0078] 15 kg of the reaction mixture was neutralized by adding 42 g of acetic acid (AcOH) (acetic acid / saponification catalyst = 1 / 1 molar ratio) and 0.1 kg of water. Argon gas was blown into the neutralization tank 1, and the reaction mixture was concentrated while removing 12.9 kg of methanol to the outside of the neutralization tank 1 at an internal temperature of 100°C.
[0079] Then, 0.76 kg of water (distilled water, electrical conductivity 4 μS / cm) was added into the neutralization tank 1 to produce an ethylene-vinyl alcohol (EVOH) solution having a weight ratio of methanol to water of 6:4 and a total solids content (TSC) of 30%.
[0080] Thereafter, an EVOH cake was produced and crushed in the same manner as in Example 1, and then washed with water five times to finally obtain a crumb-like EVOH copolymer with a water content of 68% by weight.
[0081] Comparative Example 3 An ethylene-vinyl acetate copolymer having an ethylene content of 32 mol % was saponified in the same manner as in Example 1 to obtain a reaction mixture containing an ethylene-vinyl alcohol (EVOH) copolymer.
[0082] 15 kg of the reaction mixture was neutralized by adding 42 g of acetic acid (AcOH) (acetic acid / saponification catalyst = 1 / 1 molar ratio) and 0.4 kg of water. Argon gas was blown into the neutralization tank 1, and the reaction mixture was concentrated while removing 2.5 kg of methanol to the outside of the neutralization tank 1 at an internal temperature of 100°C.
[0083] Then, 7.4 kg of water (distilled water, electrical conductivity 4 μS / cm) was added into the neutralization tank 1 to produce an ethylene-vinyl alcohol (EVOH) solution having a weight ratio of methanol to water of 6:4 and a total solids content (TSC) of 5%.
[0084] The EVOH solution was poured into a cooling and solidifying mold 3 and solidified at −8° C. to obtain an EVOH cake.
[0085] Thereafter, the EVOH cake was put into the crusher 4 and crushed, but the cake was not crushed into crumbs due to insufficient hardness, and the crushed product was in the form of a slurry.
[0086] The slurry was placed in a washing tank 6, and 500 parts by weight of 25°C water (distilled water, electrical conductivity 4 μS / cm) was added per 100 parts by weight of the EVOH pulverized material, followed by stirring for 2 hours, washing with water, and then deliquoring in a centrifugal deliquor 7. However, the pulverized material (slurry) was dissolved in the washing water and removed, and the EVOH in the form of fine particles passed through the filter, resulting in a considerable loss of the product.
[0087] For this reason, it was confirmed that the intended effect of the present invention could not be obtained under the above conditions.
[0088] <Experimental Example> (1) Total Solids Content (TSC) of EVOH Solution The total solids content of the EVOH solutions prepared in each of the Examples and Comparative Examples was measured by the following method.
[0089] A portion of the EVOH solution (W1) was dispensed onto an aluminum dish and dried in a vacuum oven at 75°C for 24 hours. The weight of the dried product (W2) was then measured and the TSC was calculated using the following formula.
[0090] TSC (wt%) = weight of sample after drying (W2) / weight of sample before drying (W1) × 100
[0091] (2) Residual sodium content analysis of EVOH copolymer The EVOH copolymer was dried in a vacuum oven at 75 °C for 24 hours. After weighing 0.2 g of the dried sample into a vessel for a microwave sample dissolution apparatus (MDS), 3 mL of nitric acid and 0.5 mL of hydrogen peroxide solution were added, and the MDS was operated (90 bar, heated to 250 °C over 30 minutes and maintained for 15 minutes). After the reaction was completed, 0.1 mL of an internal standard solution (Sc 1,000 ppm aqueous solution) was added, and ultrapure water was added so that the total volume of the sample became 10 mL, thereby producing a sample for inductively coupled plasma optical emission spectrometry (ICP-OES).
[0092] After stabilizing the ICP-OES instrument (Optima 8300DV), the above sample was injected and analyzed under the following conditions.
[0093] <ICP-OES Analysis Conditions> RF power: 1300 W Plasma Gas Flow: 15 L / min Auxiliary Gas Flow: 0.80 L / min Internal Standard: Sc Plasma Gas, Auxiliary Gas: Ar
[0094] (3) Measurement of Electrical Conductivity of Cleaning Solution After calibrating a conductivity meter (Thermo Scientific, EUTECH COND 6+) with a standard solution of 84 μS / cm, the electrical conductivity of the cleaning solution at room temperature (25 °C) was measured. The electrical conductivities shown in Tables 1 and 2 below are average values derived after taking three aliquots of the cleaning solution to be measured and measuring their electrical conductivities respectively.
[0095]
Table 1
[0096]
Table 2
[0097] Referring to Table 1, in the case of Examples 1 and 2, the sodium content in the ethylene-vinyl alcohol copolymer was reduced by 93.5% or more after only one washing, and after three washings, the electrical conductivity of the washing solution was rapidly reduced, and only a trace amount of sodium remained.
[0098] However, in Comparative Example 1 based on the existing manufacturing method, the residual sodium content exceeded 100 ppm even after three washings, and the electrical conductivity of the cleaning solution exceeded 10 μS / cm even after five washings, confirming that the cleaning efficiency was significantly reduced compared to Examples 1 and 2.
[0099] In addition, in the case of Comparative Example 2, in which the solid content of the EVOH solution was more than 25 wt%, it was found that, although it was superior to Comparative Example 1, the residual sodium was not sufficiently removed compared to Examples 1 and 2, and the result of electrical conductivity confirmed that the cleaning efficiency was lower than that of Examples 1 and 2.
[0100] In addition, when comparing the electrical conductivity and residual sodium content by washing time for each number of washings, it was found that the electrical conductivity of the washing solution and the sodium content of the copolymer after 0.5 hours and 2 hours of washing were similar within the error range in Examples 1 and 2. Therefore, according to the present invention, it is expected that a similar washing efficiency can be obtained even if the washing time is shortened to 0.5 hours. In contrast, in Comparative Example 1, the sodium content of the copolymer gradually decreases as the washing time increases, so it is considered that a washing time of 2 hours or more is necessary for sufficient washing each time.
[0101] Therefore, according to the manufacturing method of the present invention, most of the impurities can be removed by one washing, and when the number of washings is three or more, a high-purity ethylene-vinyl alcohol copolymer can be obtained. The washing time can also be significantly reduced, and therefore, it can be confirmed from the above experimental results that the efficiency of the washing process can be significantly improved compared to the conventional manufacturing method. [Explanation of symbols]
[0102] 1: Batch neutralization tank 2: Condenser 3: Ethylene-vinyl alcohol copolymer solution cooling tank 4: Crusher 5, 7: Centrifugal drainer 6: Cleaning tank 8: Distilled water tank 9, 10: Cleaning solution tank
Claims
1. Ethylene-vinyl acetate copolymer is treated with an alkali catalyst and C 1-4 saponification in the presence of an alcohol solvent to obtain a reaction mixture comprising an ethylene-vinyl alcohol copolymer; The reaction mixture was concentrated, and then water was added to the mixture to obtain the C 1-4 preparing an ethylene-vinyl alcohol copolymer solution having an alcohol and water weight ratio of 1:9 to 9:1 and a solid content of 10% by weight to 25% by weight; cooling the ethylene-vinyl alcohol copolymer solution to produce an ethylene-vinyl alcohol copolymer cake in which the ethylene-vinyl alcohol copolymer is solidified; pulverizing the ethylene-vinyl alcohol copolymer cake to obtain an ethylene-vinyl alcohol copolymer pulverized product; and washing the pulverized material with water; The method for producing an ethylene-vinyl alcohol copolymer comprises:
2. The ethylene-vinyl alcohol copolymer solution is prepared by dissolving the ethylene-vinyl alcohol copolymer in a solvent. 1-4 The weight ratio of alcohol and water is 3:7 to 7:3; The method for producing the ethylene-vinyl alcohol copolymer according to claim 1.
3. The solid content of the ethylene-vinyl alcohol copolymer solution is 15% by weight to 20% by weight. The method for producing the ethylene-vinyl alcohol copolymer according to claim 1.
4. Said C 1-4 The alcohol is at least one selected from the group consisting of methanol, ethanol, n-propanol, isopropanol, n-butanol, and t-butanol; The method for producing the ethylene-vinyl alcohol copolymer according to claim 1.
5. The ethylene-vinyl alcohol copolymer solution is cooled to −15° C. to −1° C. The method for producing the ethylene-vinyl alcohol copolymer according to claim 1.
6. The average particle size (D50) of the pulverized ethylene-vinyl alcohol copolymer is 0.1 mm to 2.5 mm. The method for producing the ethylene-vinyl alcohol copolymer according to claim 1.
7. The water washing step is repeated 2 to 5 times. The method for producing the ethylene-vinyl alcohol copolymer according to claim 1.
8. The electrical conductivity of the cleaning liquid drained after water cleaning is 10 μS / cm or less. The method for producing the ethylene-vinyl alcohol copolymer according to claim 1 or 7.
9. The residual sodium content of the ethylene-vinyl alcohol copolymer obtained after the water washing step is 30 ppm or less. The method for producing the ethylene-vinyl alcohol copolymer according to claim 1 or 7.
Citation Information
Patent Citations
Method of producing saponified product of ethylene-vinyl acetate copolymer
JP2002012618A
Ethylene-vinyl alcohol copolymer resin composition and its manufacturing method
JP2005089483A
Modified ethylene-vinyl alcohol copolymer and its manufacturing method
JP2014051647A
Ethylene-vinyl alcohol copolymer resin composition and method for producing same
WO2013005807A1
Ethylene-vinyl alcohol copolymer resin composition and method for producing same
WO2015115511A1